KEHARUSAN PARTAI POLITIK MENDORONG HADIRNYA PARTISIPASI PUBLIK DAN TERCIPTANYA LAPISAN SOSIAL MASYARAKAT BARU DALAM ERA GLOBALISASI - Azmi Muttaqin (Universitas Wahid Hasyim Semarang, 2013)
AbstractThis paper describes the role of political parties as the ideal political machine that functions encourage public participation in the context of a democratic political system. At the same time globalization provide broad access for the citizens of the State to establish global networks. Meeting of the party's strategic role and globalization spawned a new social layer.Key Words: political parties, democracy, globalization.